Changes in Nutritional Status of Children Under Five with Acyanotic Congenital Heart Disease Left to Right Shunt Type After Defect Closure by Catheterization - Marsa Hendra Utomo; Taufiq Hidayat; Heroe Soebroto (Cardiovascular and Cardiometabolic Journal (CCJ), 2024)
Highlights: 1. The nutritional status of children with CVD after therapy is interesting to discuss especially because children antibody varies. 2. Changes in their nutrition intake after the surgery would help for future treatments with related disease and same operation. - Background: One of the impacts that occur in patients with congenital heart disease (CHD) is malnutrition. Malnutrition will affect the growth of the child. Closure therapy with catheterization can improve nutritional status after a few months. This study aims to determine the nutritional status of toddlers with simple left to right shunt-type acyanotic CHD before and after closure therapy with catheterization. Material and Methods: This study is an analytical observational study with a retrospective cohort method using medical record data involving pediatric patients less than 5 years old with simple left to right shunt-type acyanotic CHD who received closure by catheterization at Dr. Soetomo General Hospital from January 2020 to December 2020. Results: From 10 samples, the characteristics of the most samples were women (90%), age group 2-5 years (60%), and PDA abnormalities (50%). In addition, nutritional status after closure by catheterization improved. Conclusion: There was an improvement in nutritional status (W/H) after defect closure with catheterization in patients aged less than 5 years with simple left to right shunt type acyanotic CHD within several months.